Research Progress on Regulation Mechanism of Acetic Acid Metabolism in Saccharomyces cerevisiae and Breeding of Low Acetic Acid-Producing Strains - DENG Haixia, GUO Chenchen, LI Erhu (Shipin Kexue, 2023)
Acetic acid is the major volatile acid in fruit wine and an excessive content of acetic acid will seriously affect the sensory quality of fruit wine. During alcoholic fermentation, acetic acid is mainly formed by the metabolism of Saccharomyces cerevisiae. Therefore, fully understanding the regulation mechanism of acetic acid metabolism by S. cerevisiae, and breeding low acetic acid-producing strains are of great significance to solve the problem of excessive acetic acid in fruit wine. In this paper, recent progress in research on the metabolic pathways and key regulatory genes of acetic acid in S. cerevisiae is reviewed. Furthermore, this paper proposes the idea that omics technologies and quantitative trait locus mapping could be applied to explore the molecular mechanism of the regulation of acetic acid production by S. cerevisiae. Finally, the application of three functional strain-breeding methods in the breeding of low acetic acid-producing strains is summarized. This review is expected to provide a reference for obtaining excellent strains with low yield of acetic acid for precise regulation of acetic acid in fruit wine.